Simulating communication in a service-oriented architecture for V2V networks - Edgar F. Esteves (2009)
A framework based on the concept of service-oriented architectures (SOA) to Support the assessment of vehicular ad-hoc networks (VANET) is herein presented. Concepts related to SOA, as well as technologies that allow real-time data acquisition and dissemination within urban environments, and simulation tools to aid the simulation of VANET were preliminarily Studied. A two-layered architecture wits specified oil the basis of the requirements for our simulation framework resulting in the specification of a multi-agent system formed of vehicle entities that are able to communicate and interact with each other and with their surrounding environment as well. A prototypical application was implemented, which Was used to demonstrate the feasibility of the approach presented through experimental results.